2018
DOI: 10.1590/0102-311x00142617
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação escolar e constituição de identidades dos escolares: da merenda para pobres ao direito à alimentação

Abstract: This essay aims to analyze school feeding as a practice contributing to the establishment of school identities. The point of departure is a nonsystematic review of publications on school feeding and identities in Brazil's public schools. The discussion begins with the persistence of paternalistic discourses and practices that reduce school feeding to food for the poor, observed in the studies. The meanings in this paternalistic approach suggest that it appears to function as a power mechanism to brand the scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 23 publications
0
6
1
23
Order By: Relevance
“…In the last 15 years, several studies have been identified in the field of public policies on food and nutrition in Brazil, some of which have addressed the issue in a comprehensive way [4][5][6], while others have focused on the analysis of specific programs, such as the Programa Nacional de Alimentação Escolar (PNAE, National School Nutrition Program) [7][8][9][10]; the Programa Bolsa Família (PBF, Family Grant Program) [11][12][13][14]; the Programa de Aquisição de Alimentos (PAA, Food Acquisition Program) [15,16]; the government-backed economy restaurants program [17,18]; and the Sistema Nacional de Segurança Alimentar e Nutricional (SISAN, National System of Food and Nutrition Security) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, several studies have been identified in the field of public policies on food and nutrition in Brazil, some of which have addressed the issue in a comprehensive way [4][5][6], while others have focused on the analysis of specific programs, such as the Programa Nacional de Alimentação Escolar (PNAE, National School Nutrition Program) [7][8][9][10]; the Programa Bolsa Família (PBF, Family Grant Program) [11][12][13][14]; the Programa de Aquisição de Alimentos (PAA, Food Acquisition Program) [15,16]; the government-backed economy restaurants program [17,18]; and the Sistema Nacional de Segurança Alimentar e Nutricional (SISAN, National System of Food and Nutrition Security) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, comer na cantina da escola parece unir as preferências alimentares dos adolescentes ao melhor status social. Nesse sentido, um estudo qualitativo apontou que o medo de adquirir uma "identidade de pobreza e inferioridade" pode ser uma das explicações para o consumo irregular, por parte dos adolescentes, da alimentação servida em escolas públicas 18 .…”
Section: Discussionunclassified
“…Em dias de funcionamento da escola, chegam no ambiente da sala de aula, indispostas e em péssimo estado nutricional por não terem se alimentado em suas casas. Essa tem sido uma realidade relatada em estudos sobre identidade da criança pobre, alimentação e direito a educação (SILVA, et al, 2018) ou implicações da merenda no currículo escolar (BEZERRA, 2009), dentre outros. Comentários analisados trazem essa questão:…”
Section: Escola Em Tempos De Pandemia: Família Pobreza E Meritocraciaunclassified